Profil Social Media Use pada Mahasiswa Tingkat Akhir: Tinjauan Psikologi terhadap Pola Penggunaan Media Sosial - Putri Tetean; Satiningsih Satiningsih (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to describe the profile of social media use among final-year students who are in the process of writing their final projects. Social media use is understood as an individual's behavior pattern in utilizing social media to fulfill academic and psychological needs, including social interaction, information seeking, entertainment, leisure activities, expression of opinions, and communication utility. This study uses a descriptive quantitative approach with a cross-sectional design. The research subjects are final year students selected using sampling techniques in accordance with research criteria. Data collection was carried out using a social media use scale that has been tested for validity and reliability. Data analysis uses descriptive statistics to describe the level of use, distribution based on respondent characteristics, platform preferences, and general patterns of social media use. The results of the study indicate that the level of social media use is in the moderate category, which shows routine but not excessive use. Use is relatively uniform based on age and gender and is dominated by visual and fast communication platforms such as Instagram, TikTok, WhatsApp, X, and YouTube. Social media is used as a source of academic information, a means of communication, entertainment, and emotional regulation during academic stress.